2020
DOI: 10.3390/ijms21031156
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Base of Behavioral Disorders in Mucopolysaccharidoses: Transcriptomic Studies

Abstract: Mucopolysaccharidoses (MPS) are a group of inherited metabolic diseases caused by mutations leading to defective degradation of glycosaminoglycans (GAGs) and their accumulation in cells. Among 11 known types and subtypes of MPS, neuronopathy occurs in seven (MPS I, II, IIIA, IIIB, IIIC, IIID, VII). Brain dysfunctions, occurring in these seven types/subtypes include various behavioral disorders. Intriguingly, behavioral symptoms are significantly different between patients suffering from various MPS types. Mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…The question what is the specific cause of changes in expression of tested genes in MPS cells remains unanswered. As indicated in recently published reports [12–14], expression of hundreds of genes is changed in MPS cells relative to controls. Specific mechanisms of these regulations remain to be elucidated; however, it was proposed that they reflect secondary and tertiary changes in cellular processes, after primary GAG storage [32].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The question what is the specific cause of changes in expression of tested genes in MPS cells remains unanswered. As indicated in recently published reports [12–14], expression of hundreds of genes is changed in MPS cells relative to controls. Specific mechanisms of these regulations remain to be elucidated; however, it was proposed that they reflect secondary and tertiary changes in cellular processes, after primary GAG storage [32].…”
Section: Resultsmentioning
confidence: 88%
“…Thus, one might suspect that such patients might be a high risk group for COVID‐19; however, no reports were published to date on COVID‐19 in MPS. On the other hand, recent studies indicated that in cells of MPS patients, there are hundreds of genes which expression is significantly changed relative to healthy persons [12–14]. This might potentially modify susceptibility of these patients to infection by SARS‐CoV‐2.…”
mentioning
confidence: 99%
“…4), suggesting that there are groups of processes similarly changed in all these types, despite evident specificity of each type. Although experiments presented in this report were performed on fibroblasts, specific changes in expressions of regulatory proteins might, to some extent, be extrapolated to other cell types, including neurons as discussed previously (Pierzynowska et al 2020), suggesting that they could contribute to neurodegenerative processes occurring in MPS.…”
Section: Discussionmentioning
confidence: 89%
“…Recent studies clearly indicated that secondary and tertiary changes (after the primary GAG storage) in cellular processes contribute significantly to the development of disorders and symptoms appearing in the course of MPS (Gaffke et al 2019;Fecarotta et al 2020). Significance of this aspect of MPS pathomechanism has been highlighted recently by discoveries of multiple changes in expression of genes coding for proteins involved in various cellular mechanisms in MPS (Brokowska et al 2020;Gaffke et al 2020;Pierzynowska et al 2020;Rintz et al 2020). Therefore, in this work, we have analyzed transcriptomic data, focusing on expression of genes coding for regulatory proteins responsible for the control of cellular processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation